Automated Waves Files Splitting (International Journal of Innovative Research in Computer Science & Technology, 2021)
The ASS (Automatic Speech Segmentation) Technique is used in this article to  segment spontaneous speech into syllable-like units. The  segmentation of the acoustic signal into syllabic units is  an essential step in the construction of a syllable-centric  ASS system. The purpose of this article is to determine  the smallest unit of speech that should be regarded when  writing. Any voice recognition system may be trained. In  a few Indian cities, technologies for continuous voice  recognition have been created. Hindi and Tamil are  examples of such languages. This article examines the  statistical characteristics of Punjabi syllables and how  they may be used to reduce the number of syllables in  sentence. During voice recognition, the search area is  expanded. We explain how to perform the majority of the  segmentation in this article automatically. The frequency  of syllables and the number of syllables in each word are  shown. We suggest the following: For objective  evaluation of stuttering disfluencies, an automated  segmentation technique for syllable repetition in read  speech was developed. It employs a novel method and  consists of three stages: feature extraction, rule matching,  and segmentation.
Keywords: ASS; Segmentation; Syllables; Splitting; Wave